Glial fibrillary acidic protein in late life major depressive disorder: an immunocytochemical study. Issue 5 (1st November 2002) - Davis, S; Thomas, A; Perry, R; Oakley, A; Kalaria, R N; O'Brien, J T
Abstract : Objectives: Depression is a common psychiatric disorder in late life. Cerebrovascular disease has been postulated as an important aetiological factor in many cases (the "vascular depression" hypothesis). Consistent with this, an inflammatory response, most probably representing ischaemia, has been reported with increases in intercellular adhesion molecule 1 (ICAM-1), in the dorsolateral prefrontal cortex (DLPFC) in postmortem tissue from elderly depressed subjects. As ischaemia is known to cause astrogliosis, this study has further tested the "vascular depression hypothesis" by investigating the distribution of the astrocytic marker glial fibrillary acidic protein (GFAP) in the DLPFC and in the anterior cingulate cortex (ACC). Methods: Postmortem tissue was obtained from 20 elderly patients with a history of major depressive disorder (MDD) and 20 control subjects. Sections were stained for GFAP using standard immunocytochemistry. Sets of images were obtained from all cortical layers in the DLPFC and ACC with the exception of layer IV in the ACC, and from gyral and deep white matter in both regions. The percentage of the area of each image occupied by GFAP was calculated using true colour image analysis, and mean values obtained for each region examined. Results: Immunoreactivity for GFAP was low in grey matter (for example, Mean (SEM) 0.76 (0.2)% in DLPFC layer V in depressed subjects), but higher in white matter (for example, 12.02 (2.2)% in DLPFC deep white matter in depressed subjects). Pronounced gliosis was observed within grey matter in a few cases only. GFAP immunoreactivity was significantly higher in layer I of the DLPFC in depressed subjects 15.8 (2.6)% than in controls 9.7 (1.3)% ( t =2.2; df=27.5, p=0.04). No difference was detected in any other region. Conclusions: The data suggest any increase in GFAP in elderly MDD patients is limited to layer 1 of the DLPFC. These results provide some support for the vascular depression hypothesis and further implicate DLPFC abnormalities in depression.